New genera and species of leaf beetles (Coleoptera: Chrysomelidae) from China and South Korea - Lopatin, I. K.; Konstantinov, A. S. (Zootaxa, 2009)
Two new genera from China (Taumaceroides Lopatin and Yunnaniata Lopatin) and 11 new species (Smaragdina quadrimaculata Lopatin, S. oblongum Lopatin, Hyphaenia volkovitshi Lopatin, Arthrotus daliensis Lopatin, Taumaceroides sinicus Lopatin, Yunnaniata konstantinovi Lopatin, Calomicrus yunnanus Lopatin, C. minutissimus Lopatin, Hermaeophaga belkadavi Konstantinov, H. dali Konstantinov from China, and H. korotyaevi Konstantinov from South Korea) are described and illustrated. A key to Hermaeophaga species of Eurasia is presented. Since Hermaeophaga dali was collected feeding on Paederia foetida L. (Rubiaceae), which is an invasive noxious weed in the United States, this species has potential as a biological control agent of this weed.